High dose methylprednisolone in severe acute transverse myelopathy. Issue 2 (1st February 1997) - Sébire, Guillaume; Hollenberg, Henri; Meyer, Laurence; Huault, Gilbert; Landrieu, Pierre; Tardieu, Marc
Abstract : No effective treatment has been shown for patients with acute transverse myelopathy. In an open study five children with severe acute transverse myelopathy were treated with intravenous methylprednisolone and compared with a historical group of 10 patients. The results show that in the methylprednisolone treatment group compared with the historical group of 10 patients: the median time to walk independently was significantly reduced (23 v 97 days); the proportion of patients with a full recovery within 12 months was significantly higher (80 v 10%); all patients had complete motor recovery within one year in contrast with only two of 10 patients in the historical group; and serious adverse effects did not occur. This pilot study suggests that high dose methylprednisolone is effective in the treatment of acute transverse myelopathy.